PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN DAN PERTUMBUHAN PENJUALAN TERHADAP PERTUMBUHAN LABA - Trisandi Eka Putri; Andriansyah Andriansyah (JASS (Journal of Accounting for Sustainable Society), 2022)
The purpose of this research is to see the effect of capital structure, company size, and sales growth on profit growth. This study was conducted on health and care sector companies listed on Bursa Malaysia from 2017-2020. The research method in this study used the classical assumption of normality test, multicollinearity test, autocorrelation test, and heteroscedasticity test. Multiple regression analysis is used to process sample data, with sampling using the purposive sampling method. The results showed that the data used were normally distributed and no symptoms of multicollinearity, autocorrelation, or heteroscedasticity. Sales growth has a significant effect on profit growth, while the capital structure and company size have no significant impact on profit growth. Simultaneously capital structure, company size, and sales growth have a significant effect on profit growth.